The Complex Influences on How We Care for Farmed Fish - Turnbull, James F. (Frontiers in Veterinary Science, 2022)
As a veterinarian and academic in aquaculture, in my personal experience most farmers are concerned for their animals and want to take good care of them. There has been substantial improvement in the welfare of farmed fish in recent decades, but improvements have been inconsistent across culture systems and species. Where there has been a lack of progress it is not simply due to the more obvious barriers, for example, lack of clear messages, lack of effective dissemination or cost of implementation. Why have the good intentions of farmers and research by academics failed to improve the care of many farmed fish? The reasons would appear to be complex, however, human behavioural theory (this term used to differentiate from animal ethology), offers both a conceptual framework and practical guidelines for improving the care of fish by influencing the behaviour of farmers. Here I present some background context and apply human behavioural theory to examples of on-farm care of fish.